The Sacred Vows of Marriage Were Tainted: Study of Christian Domestic Violence in Hinekombe Village, Papua - Gainau, Markus Samson (BIA': Jurnal Teologi dan Pendidikan Kristen Kontekstual, 2024)
Abstract: Violence in the Christian family is the most widespread type of gender-based violence that draws attention from the Church. Domestic violence is an act of hostility toward God. This study seeks to explore domestic violence in Papua from a Christian standpoint. This research uses a qualitative approach with a case study method. Researchers used in-depth interviews, observations, and documentation studies to collect data in this study. The research found two things: First, domestic violence is clear evidence of violating the sacred promise of marriage. Through the research results, it was found that in the indigenous Papuan community in Hinekombe village, there are traditions regarding male dominance over women and tolerance of the use of force by men. Secondly, God cares deeply about Christian marriage. God emphasizes that it is in the family that one can shape his or her personality and build a relationship with God. Marriage is "an honourable treasure ordained and blessed by God," a model of the relationship between Christ and the Church, and a union meant for "mutual harmony" where "men and women can please each other, not hurt.Â Keywords: Sacred Vows of Marriage, Tainted, Christian Domestic Violence, Hinekombe Village, Papua.